Pendampingan Penyusunan Laporan Keuangan Akuntansi Pesantren - Valentina Monoarfa (Mopolayio : Jurnal Pengabdian Ekonomi, 2021)
Islamic boarding school is one of the educational institutions of non-governmental non-profit religious organizations that prioritizes a service to external parties. The financial management of Islamic boarding schools still uses simple methods, accounting that has been used so far has not used financial reports that are in accordance with Islamic boarding school accounting guidelines. The purpose of this service is to provide additional knowledge to financial managers in compiling financial reports using software in order to provide transparent, accountable and accountable reporting. The method of implementing the activity is counseling, discussion and question and answer, which begins with providing knowledge about how to prepare Islamic boarding school accounting financial reports.